Neohookean deformations of annuli in the higher dimensional Euclidean space. (December 2019) - Zhu, Jian-Feng; Kalaj, David
Abstract: Let n > 2 be an integer and assume that A = x ∈ R n : 1 < | x | < R and A ∗ = y ∈ R n : 1 < | y | < R ∗ be two annuli in Euclidean space R n . Assume that F ( A, A ∗ ) (resp. R ( A, A ∗ ) ) be the class of all orientation preserving (resp. radial) homeomorphisms h : A ↦ A ∗ in the Sobolev space W 1, n ( A, A ∗ ) which keep the boundary circles in the same order. In this paper, we extended the corresponding results of Iwaniec and Onninen which was published in Math. Ann Vol. 348, 2010.